Hyperoxygenation as a Therapeutic Supplement for Treatment of Triple Negative Breast Cancer - Mast, Jesse M.; Kuppusamy, Periannan (Frontiers in Oncology, 2018)
Triple-negative breast cancer (TNBC) refers to a group of biologically aggressive breast cancers that do not express estrogen, progesterone or epidermal growth factor receptor 2 hormone receptors. Each subset of TNBC has a unique molecular profile and may require specific treatments. A combination of surgery and chemotherapy followed by radiation therapy is the standard treatment mode for TNBC patients. Tumor oxygen status (hypoxia) is a key factor that may compromise the effectiveness of radiation treatment, as it is known that hypoxia can confer radiation resistance. In this study, we characterized MDA-MB-231 orthotropic xenograft tumors with respect to tumor oxygen level and their response to supplemental oxygen therapy in combination with paclitaxel and radiation therapy. We observed that the TNBC tumors became severely hypoxic (pO2 < 4 mmHg) within 1 week of tumor growth and responded poorly to administration of respiratory hyperoxygenation (100% O2) to mitigate hypoxia. However, periodic administration of supplemental oxygen (100% O2; 60 min/day for 21 days) showed a significant inhibitory effect on tumor volume when compared to control (102332 mm3 versus 1378114 mm3; p<0.05). Combination of supplemental oxygen with paclitaxel and radiation therapy led to a significant reduction in tumor growth when compared to radiation alone (23940 mm3 versus 39032 mm3; p<0.05). The therapeutic enhancement by supplemental oxygen is possibly attributed to increase in tumor oxygenation with paclitaxel at the time of radiation treatment. These findings may have important implications in the understanding the role of oxygen and supplemental oxygen therapy for the treatment of TNBC patients.